Black Americans' perceptions of Alzheimer's disease, a healthy brain, and strategies for brain health promotion - Johanne Eliacin; Angelina Polsinelli; Kenzie A. Cameron; Andrew J. Saykin; Sophia Wang (Elsevier, 2024)
Objectives: Lack of awareness of Alzheimer's disease (AD) among Black Americans may undermine their ability to identify potential AD risk. We examined Black Americans' perceptions and knowledge of AD, and views of a healthy brain, which may contribute to the development of effective and culturally sensitive strategies to address racial disparities in AD. Methods: We conducted a mixed-methods study, integrating a cross-sectional survey of 258 older (>55 years) Black participants and qualitative interviews with a sub-sample of N = 29. Both data sets were integrated to inform the results. Results: Participants endorsed having little knowledge of AD. While most participants reported practicing a healthy lifestyle to promote a healthy brain, the range of activities listed were limited. Participants made several suggestions to increase AD awareness, which includes using AD educational materials containing information that would benefit the whole family, not only older adults. Outreach approaches that address both individual behaviors and structural factors were also encouraged. Conclusion: Our findings identify ongoing needs to improve AD awareness among traditionally under-represented groups. Innovation: The study utilized novel approaches to examine participants' perspectives of AD that included a diverse sample of research naïve participants, and integrated exploration of participants' views of AD and brain health.